Educational ideas of Camilo Osias - Antonio, Eleanor M. (Dallo) 1946- (s.n.], 1971)
The views of Camilo Osias, an acknowledged educator on the success and failure of the Philippine educational system, was obtained. Because of his special position in the educational, political, and civic spheres, he could provide a crystallization of his ideas on education after over fifty years of intimate study, observation, and support of its regulations, policies, and direction. Because of Osias' involvement in the first Constitutional Convention and his interest in the 1971 Convention, the time was opportune to ask him to review his view and forecast new provisions.